The effect of the Lokomat® robotic-orthosis system on lower extremity rehabilitation in patients with stroke: a systematic review and meta-analysis - Wu, Lina; Xu, Gui; Wu, Qiaofeng (Frontiers in Neurology, 2023)
The Lokomat® is a device utilized for gait training in post-stroke patients. Through a s ystematic review, the objective was to determine whether robot-assisted gait training with the Lokom at® is more effective in enhancing lower extremity rehabilitation a stroke in comparison to conventio nal physical therapy (CPT). Methods: In this study, a systematic search was conducted in various dat abases, including CINAHL, MEDLINE, PubMed, Embase, Cochrane Library, Scopus, Web of Scien ce, and Physiotherapy Evidence Database (PEDro), as well as bibliographies of previous meta-analys es, to identify all randomized controlled trials that investigated the use of Lokomat® devices in adult stroke patients. The study aimed to derive pooled estimates of standardized mean differences for six outcomes, namely Fugl-Meyer Assessment lower-extremity subscale (FMA-LE), Berg Balance Scale (BBS), Gait Speed, functional ambulation category scale (FAC), Timed Up and Go (TUG), and Fun ctional Independence Measure (FIM), through random effects meta-analyses. Results: The review an alyzed 21 studies with a total of 709 participants and found that the use of Lokomat® in stroke patien ts resulted in favorable outcomes for the recovery of balance, as measured by the BBS (mean differen ce = 2.71, 95% CI 1.39 to 4.03; p < 0.0001). However, the FAC showed that Lokomat® was less effe ctive than the CPT group (mean difference = -0.28, 95% CI -0.45 to 0.11, P = 0.001). There were no significant differences in FMA-LE (mean difference = 1.27, 95% CI -0.88 to 3.42, P = 0.25), Gait Sp eed (mean difference = 0.02, 95% CI -0.03 to 0.07, P = 0.44), TUG (mean difference = -0.12, 95% C I -0.71 to 0.46, P = 0.68), or FIM (mean difference = 2.12, 95% CI -2.92 to 7.16, P = 0.41) between t he Lokomat® and CPT groups for stroke patients. Conclusion: Our results indicate that, with the exc eption of more notable improvements in balance, robot-assisted gait training utilizing the Lokomat® was not superior to CPT based on the current literature.